FA2H Exhibits Tumor Suppressive Roles on Breast Cancers via Cancer Stemness Control - Dai, Xiaofeng; Zhang, Shuo; Cheng, Hongye; Cai, Dongyan; Chen, Xiao; Huang, Zhaohui (Frontiers in Oncology, 2019)
Background: Triple negative breast cancers are aggressive, enriched with cancer stem cells, and lack effective targeted therapies with little side effects. Methods: We isolated cancer stem cells from two triple negative breast cancer cell lines via cell sorting following transcriptome sequencing, bioinformatics analysis, experimental and clinical validations, as well as functional investigations to explore genes capturing triple negative breast cancer features for improved diagnosis and therapeutics in clinics. Results: We found that FA2H is under-expressed in triple negative breast cancers both in vitro and in clinics, and FA2H suppresses cancer stemness via inhibiting the STAT3/IL6 axis and NFkB signaling. Conclusions: This study reports the tumor suppressive roles of FA2H on breast cancer cells through cancer stemness control. FA2H and other candidates unveiled in this study that capture the features of cancer stem cells may contribute as diagnostic marker and/or effective therapeutic targets for improved triple negative breast cancer management.